The rise of modern China based on the magazine “China reconstructs” - Anastasia G. Liulina; Maia A. Egorova (RUDN Journal of World History)
The significance of the research topic is determined by the relevance of the problem of soft power in China’s foreign policy and foreign economic policy at present. The purpose of this research project is to trace the origins of the concept of soft power , based on the materials and articles of the international Chinese magazine China Reconstructs (1952-1990). During the historical period under study, China was transitioning from the model of a closed state to positioning itself as one of the world leaders; the gradual transition to an open country required the activation of soft power policy in order to recognize legitimacy and strengthen its role on the world stage. The main stages of the history of New China’s development were not only reflected in the pages of the magazine, but also changed the magazine itself and its ideological content, which was broadcasting to the outside world. The authors conclude that soft power began to emerge since the formation of the People’s Republic of China and dates back to the reign of Mao Zedong. The authors consider the China Reconstructs magazine as an important tool of China’s soft power of that period, which is confirmed by the editorial guidelines of the magazine and the content of the articles.